Suicide in U.S. Workplaces, 2003–2010: A Comparison With Non-Workplace Suicides - Tiesman, Hope M. (Am J Prev Med, 2015)
INTRODUCTION: Suicide rates have risen considerably in recent years. National workplace suicide trends have not been well documented. The aim of this study is to describe suicides occurring in U.S. workplaces and compare them to suicides occurring outside of the workplace between 2003 and 2010. METHODS: Suicide data originated from the Census of Fatal Occupational Injury database and the Web-Based Injury Statistics Query and Reporting System. Suicide rates were calculated using denominators from the 2013 Current Population Survey and 2000 U.S. population census. Suicide rates were compared among demographic groups with rate ratios and 95% CIs. Suicide rates were calculated and compared among occupations. Linear regression, adjusting for serial correlation, was used to analyze temporal trends. Analyses were conducted in 2013–2014. RESULTS: Between 2003 and 2010, a total of 1,719 people died by suicide in the workplace. Workplace suicide rates generally decreased until 2007 and then sharply increased (p=0.035). This is in contrast with non-workplace suicides, which increased over the study period (p=0.025). Workplace suicide rates were highest for men (2.7 per 1,000,000); workers aged 65–74 years (2.4 per 1,000,000); those in protective service occupations (5.3 per 1,000,000); and those in farming, fishing, and forestry (5.1 per 1,000,000). CONCLUSIONS: The upward trend of suicides in the workplace underscores the need for additional research to understand occupation-specific risk factors and develop evidence-based programs that can be implemented in the workplace.